2021
DOI: 10.1083/jcb.202103033
|View full text |Cite
|
Sign up to set email alerts
|

CHMP2B regulates TDP-43 phosphorylation and cytotoxicity independent of autophagy via CK1

Abstract: The ESCRT protein CHMP2B and the RNA-binding protein TDP-43 are both associated with ALS and FTD. The pathogenicity of CHMP2B has mainly been considered a consequence of autophagy–endolysosomal dysfunction, whereas protein inclusions containing phosphorylated TDP-43 are a pathological hallmark of ALS and FTD. Intriguingly, TDP-43 pathology has not been associated with the FTD-causing CHMP2BIntron5 mutation. In this study, we identify CHMP2B as a modifier of TDP-43–mediated neurodegeneration in a Drosophila scr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…1 a-b’). Since TDP-43 pathology is often associated with hyperphosphorylation [ 38 , 39 ] and the phosphorylation state of TDP-43 protein is positively correlated with its toxicity [ 40 42 ], we focused on the fly genes encoding protein kinases and phosphatases in one set of the transgenic RNAi screen. Among them, we found that two independent RNAi lines (#28,685 and #31,184) of the gene Dsor1 , the Drosophila homologue of mammalian MEK ( dMEK ), showed dramatic suppression of the age-dependent eye degeneration of the TDP-43 flies (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 a-b’). Since TDP-43 pathology is often associated with hyperphosphorylation [ 38 , 39 ] and the phosphorylation state of TDP-43 protein is positively correlated with its toxicity [ 40 42 ], we focused on the fly genes encoding protein kinases and phosphatases in one set of the transgenic RNAi screen. Among them, we found that two independent RNAi lines (#28,685 and #31,184) of the gene Dsor1 , the Drosophila homologue of mammalian MEK ( dMEK ), showed dramatic suppression of the age-dependent eye degeneration of the TDP-43 flies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To our surprise, neither the phosphorylation levels (ratio of pTDP-43 to total TDP-43) nor the abundance of pTDP-43 proteins (normalized to GAPDH) was significantly altered by RNAi- Dsor1 (Figure S 3 c, d) or RNAi- rl (Figure S 3 g, h). In addition, transgenically expressed wild-type (WT) hTDP-43 was soluble and did not result in insoluble aggregation in fly models (Figure S 3 i; and [ 42 , 44 , 45 ]), which excluded the possibility that the mitigating effect by downregulation of Dsor1 or rl was due to reducing hTDP-43 protein aggregates.…”
Section: Abnormal Upregulation Of Rl and The Mek/e...mentioning
confidence: 99%
“…Our study is the first to establish a PRG-based predictive nomogram model to predict the risk of periodontitis from a molecular perspective. CHMP2B, a nuclear member of the endosomal sorting required for transport complex III, is integral to endolysosomal trafficking, vesicle fusion, and autophagic degradation [ 30 ]. It resides in chromosome 3p11-12 region near VGLL3 gene, which shows amplification in diverse sarcomas [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CHMP2B has recently been demonstrated to regulate the phosphorylation of TDP‐43 via CK1. Moreover, knockdown of CHMP2B prevented toxicity associated with TDP‐43 overexpression in both Drosophila and mammalian cell models [167]. This observation may challenge initial documentation that TDP‐43 pathology is not a defining feature of CHMP2B FTD [159,160,163,168,169].…”
Section: The Escrt Pathway and Its Relationship To Neurodegenerative ...mentioning
confidence: 99%